Radiosensitivity of Some Local Cultivars of Wheat (Triticum Aestivum L.) to Gamma Irradiation (Bangladesh Journal of Botany, 2012)
Seeds of four local wheat (Triticum aestivum L.) cultivars, namely Hinta, Khaliji, Lokaimy and Qasime collected from different regions of Saudi Arabia were exposed to different doses of gamma rays 50-500 Gy to determine suitable doses for induction of mutation. It was observed that seedling height decreased with the increased dose of radiation in all cultivars. Radiosensitive curve originated from seedling height data resulted in 179, 225, 249 and 256 Gys as LD50 values for the cultivars Hinta, Khaliji, Qasime and Lokaimy, respectively. Based on LD50, as to minimize DNA damage and reduce undesirable mutations, radiation doses which lie between 200 and 250 Gy can be considered suitable for induction of mutation in cultivars Lokaimy, Khaliji and Qasime while between 150 and 200 Gy for cultivar Hinta DOI: http://dx.doi.org/10.3329/bjb.v41i1.11075 Bangladesh J. Bot. 41(1): 1-5, 2012 (June)